Cat about town - Conte, Cate (Conte, Cate, Cat café mystery., 2017)
"The first novel in a frisky new mystery series set in a small New England town, where an unlikely citizen is called in to solve the purrfect crime. . . Maddie James has arrived in Daybreak Island, just off the coast of Massachusetts, eager to settle down and start her own business--and maybe even fall in love. When a stray orange tabby pounces into her life, she's inspired to open a cat café. But little does Maddie know that she's in for something a lot more catastrophic when her new furry companion finds the dead body of the town bully. Now all eyes are on Maddie: Who is this crazy cat-whisperer lady who's come to town? If pet-hair-maintenance and crime-fighting weren't keeping her busy enough, Maddie now has not one but two eligible bachelors who think she's the cat's pajamas . . . and will do anything to win her heart. But how can she even think about happily-ever-after while a killer remains on the loose--and on her path?"--Page 4 of cover.